Cancer‐associated venous thromboembolism: Incidence and features in a racially diverse population. (7th August 2022) - Raskob, Gary E.; Wendelboe, Aaron M.; Campbell, Janis; Ford, Lance; Ding, Kai; Bratzler, Dale W.; McCumber, Micah; Adamski, Alys; Abe, Karon; Beckman, Michele G.; Reyes, Nimia L.; Richardson, Lisa C.
Abstract: Background: Data on the population‐based incidence of cancer‐associated venous thromboembolism (VTE) from racially diverse populations are limited. Objective: To evaluate the incidence and burden of cancer‐associated VTE, including demographic and racial subgroups in the general population of Oklahoma County—which closely mirrors the United States. Design: A population‐based prospective study. Setting: We conducted surveillance of VTE at tertiary care facilities and outpatient clinics in Oklahoma County, Oklahoma, from 2012–2014. Surveillance included reviewing all imaging reports used to diagnose VTE and identifying VTE events from hospital discharge data and death certificates. Cancer status was determined by linkage to the Oklahoma Central Cancer Registry. Measurements: We used Poisson regression to calculate crude and age‐adjusted incidence rates of cancer‐associated VTE per 100 000 general population per year, with 95% confidence intervals (95% CI). Results: The age‐adjusted incidence (95% CI) of cancer‐associated VTE among adults age ≥ 18 was 70.0 (65.1–75.3). The age‐adjusted incidence rates (95% CI) were 85.9 (72.7–101.6) for non‐Hispanic Blacks, 79.5 (13.2–86.5) for non‐Hispanic Whites, 18.8 (8.9–39.4) for Native Americans, 15.6 (7.0–34.8) for Asian/Pacific Islanders, and 15.2 (9.2–25.1) for Hispanics. Recurrent VTE up to 2 years after the initial diagnosis occurred in 38 of 304 patients (12.5%) with active cancer and in 34 of 424 patients (8.0%) with a history of cancer > 6 months previously. Conclusion: Age‐adjusted incidence rates of cancer‐associated VTE vary substantially by race and ethnicity. The relatively high incidence rates of first VTE and of recurrence warrant further assessment of strategies to prevent VTE among cancer patients.